Забезпечення завадостійкості БПЛА за рахунок використання UWB технології - Рудь. Д. М. (ХНУРЕ, 2024)
The use of UWB technology to increase bandwidth and ensure immunity to data transmission over communication channels between the "drone" and any control point is considered. The topology and energy characteristics of a microstrip logarithmic spiral antenna for placement on board an aircraft were developed and analyzed.
Keywords: забезпечення завадостійкості БПЛА; UWB технології